Subjectively and objectively assessed social and physical environmental correlates of preschoolers’ accelerometer-based physical activity - Eichinger, Michael; Schneider, Sven; Bock, Freia de (International journal of behavioral nutrition and physical activity, 2017)
Overweight and low levels of physical activity (PA) in preschoolers are major public health concerns. However, to date only few studies have investigated subjective and objective correlates of PA across different socioecological domains in preschoolers. We therefore simultaneously investigate associations between preschoolers’ objectively measured leisure-time PA and a comprehensive set of subjective and objective potential PA correlates across the behavioral, social and physical environmental domains on both family- and community-level.